Integrated Nanofiltration and Upflow Anaerobic Sludge Blanket Treatment of Textile Wastewater for In-Plant Reuse - Gomes, Arlindo Caniço (2010)
The filtration characteristics of simulated dyeing effluents containing Acid Orange 7, sodium sulfate, and a pH buffer made of acetic acid and sodium acetate is described using a commercially available nanofiltration membrane. The original membrane filtration properties were characterized with deionized water to provide a baseline of membrane performance. At high volumetric concentration of the test solutions, greater than 98% rejection of dye and sodium sulfate were obtained. Rejection of buffering chemicals was approximately 50% in all experiments, giving a permeate water not suitable for reuse in most dyeing operations. The final composite concentrate had a chemical oxygen demand (COD) value .2000 mg/L. No problems were encountered with anaerobic treatment of the concentrate obtained from the dyeing wastewater. Adjusting the sulfate concentration to give COD-to-sulfate ratios to 2.9, 5.4, and 18.2 in the reactor feed had no significant alterations in the performance of the upflow anaerobic sludge blanket reactor.